If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 3) + -2(y + -1) = 0 Reorder the terms: 3(3 + y) + -2(y + -1) = 0 (3 * 3 + y * 3) + -2(y + -1) = 0 (9 + 3y) + -2(y + -1) = 0 Reorder the terms: 9 + 3y + -2(-1 + y) = 0 9 + 3y + (-1 * -2 + y * -2) = 0 9 + 3y + (2 + -2y) = 0 Reorder the terms: 9 + 2 + 3y + -2y = 0 Combine like terms: 9 + 2 = 11 11 + 3y + -2y = 0 Combine like terms: 3y + -2y = 1y 11 + 1y = 0 Solving 11 + 1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 1y = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 1y = 0 + -11 1y = 0 + -11 Combine like terms: 0 + -11 = -11 1y = -11 Divide each side by '1'. y = -11 Simplifying y = -11
| x+9=-3*2 | | 23=16+7q | | 23=16+7a | | 2.2x-7-1.6x=0.6x-7 | | 2(x+4)=3x-1*5 | | 7g-1=13-5g | | n-6=2-3n | | -4y+8(7y-2)=5-4(-4-y) | | Y-44=-27 | | x+4=20x | | x+4=10x | | 2a(a-5)+4(a-5)=a | | 101(3a-1)=149 | | 7(x+20)=x+2 | | D-6=-9 | | -5(3p+3)= | | 0=x^2-5x-5 | | (8x+9)(3x-4)=0 | | (x+7)*.05+.4=.1x | | y=x^2-5x-5 | | 5(16-n)+100n=1125 | | 2x=m | | 2x-8x+5x-4x= | | 4n-3n-7=44 | | -2(x+5)=2(x-1) | | -2(4-3)=6 | | 100-80= | | 4n-3n-7=54 | | 0.4x-0.5(2x+7)=0.7(x+3) | | 2+35324= | | -66=-11g+33 | | -4a+24+6a=3a-7a |